Criminal Politics (Enforcement) of Criminal Law Based on Pancasila Equity - Rasdi Rasdi (Universitas Negeri Semarang, 2020)
Indonesian state based on Pancasila, any rule of law (criminal) and their enforcement should always contains/is inspired by the values of Pancasila. The policy of enforcing criminal law means upholding justice, and the justice for the Indonesian people is equity based on Pancasila. The direction and policies for the development of national law (criminal law) in realizing the ideals of legal development based on justice should always be based on religious values, customs and socio-cultural values of Indonesian society which crystallized in the Pancasila philosophy. Therefore, the essence of criminal law policy is that efforts to achieve social welfare should always be inspired by and based on the basic values of the Pancasila philosophy as Grundnorm / Staatsfundamentalnorm (fundamental norms of the state) of the Indonesian nation. Pancasila is the values, principles, soul and spirit of the Indonesian people. Pancasila is the basic norm (grundnorm), and at the same time the basic values (grundwerten), which are the spirit of Indonesian law. Law is always rooted in